Taxonomy, Nomenclature and Lectotypifications of Photinia lindelyana Wight & Arn. (Rosaceae): an Endemic to Nilgiri Biosphere Reserve, Southern Western Ghats, India - Kumar, K. Sampath; Arumugam, S. (Indian Forester, 2022)
No Abstract.